2017
DOI: 10.1186/s12916-017-0853-1
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous intervention versus coronary artery bypass graft surgery in left main coronary artery stenosis: a systematic review and meta-analysis

Abstract: BackgroundThe optimal revascularization technique in patients with left main coronary artery disease (CAD) remains controversial. We aimed to compare the long-term performance of percutaneous coronary intervention (PCI) versus coronary artery bypass graft (CABG) surgery in treatment of left main CAD.MethodsPubMed, EMBASE, and the Cochrane Library were searched until November 16, 2016.ResultsSix randomized controlled trials and 22 matched observational studies including 22,487 patients and 90,167 patient-years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…Previous studies have compared the two revascularization strategies and found different results than those observed in the current study. Although no separate analysis of diabetic cohorts was performed, a meta-analysis by Zhang et al [35] suggested that PCI, with newer generation DES, might be a safe alternative revascularization strategy for left main CAD. However, it was noted that this method presented a higher risk of repeat revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have compared the two revascularization strategies and found different results than those observed in the current study. Although no separate analysis of diabetic cohorts was performed, a meta-analysis by Zhang et al [35] suggested that PCI, with newer generation DES, might be a safe alternative revascularization strategy for left main CAD. However, it was noted that this method presented a higher risk of repeat revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary atherosclerosis causes blockage of the coronary arteries, leading to myocardial ischemia, myocardial infarction (MI), and ischemic cardiomyopathy. Current medical interventions for IHD include pharmacologic therapy (antiplatelet drugs, β-blockers, or statins) for disease stabilization and reduction of acute events (e.g., myocardial infarction or sudden death) or immediate restoration of the blood supply via surgical treatment, such as coronary artery bypass graft (CABG) surgery and percutaneous coronary intervention (PCI), two of the most common revascularization procedures performed worldwide [3,4]. However, a significant number of patients are clinically refractory to medical therapy and are ineligible to receive either PCI or CABG due to the patient's clinical condition or to technological limitations of currently available therapies [2,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…These drugs are used for condition stabilization and reduction of acute events. Alternatively, the blood supply can be restored immediately by surgical treatment [ 7 , 8 ]. However, the reperfusion paradoxically causes further myocardial contractile dysfunction and cardiomyocyte death, a phenomenon known as ischemia/reperfusion (I/R) injury.…”
Section: Introductionmentioning
confidence: 99%